2001
DOI: 10.1097/00005392-200104000-00010
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a 4 Cm. Cutoff Point for Stratification of T1n0m0 Renal Cell Carcinoma After Radical Nephrectomy

Abstract: Tumor size is an important prognostic factor for patients with T1N0M0 renal cell carcinoma. A cutoff point of 4 cm. is practical for dividing the T1N0M0 classification into T1a and T1b subclasses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
10

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 15 publications
1
13
0
10
Order By: Relevance
“…Several authors [3,4] have indicated that in terms of prognosis, grouping tumours that vary so broadly in size under a single stage classification does not change cancer-specific survival. However, in accordance with other authors (table 2) [5][6][7][8][9][10] who have proposed a re-evaluation of the 1997 TNM classification using different cut-offs (ranging between 4 and 5.5 cm) that correlated better with clinical outcome than 7 cm, we deciced to review our experience in this regard. We also performed this study in order to determine if there were any differences in terms of cancer-specific survival by dividing stage pT1 into two different groups employing different cut-off point sizes of 0.5 cm (from 2.5 to 5 cm); however, there was a slight statistical significance only for a cut-off of 5 cm (p = 0.2844).…”
Section: Discussionsupporting
confidence: 68%
“…Several authors [3,4] have indicated that in terms of prognosis, grouping tumours that vary so broadly in size under a single stage classification does not change cancer-specific survival. However, in accordance with other authors (table 2) [5][6][7][8][9][10] who have proposed a re-evaluation of the 1997 TNM classification using different cut-offs (ranging between 4 and 5.5 cm) that correlated better with clinical outcome than 7 cm, we deciced to review our experience in this regard. We also performed this study in order to determine if there were any differences in terms of cancer-specific survival by dividing stage pT1 into two different groups employing different cut-off point sizes of 0.5 cm (from 2.5 to 5 cm); however, there was a slight statistical significance only for a cut-off of 5 cm (p = 0.2844).…”
Section: Discussionsupporting
confidence: 68%
“…Krejci et al 8 correlated tumor size with cause-specific survival and proposed a 5.0-cm size cutoff to separate T1a and T1b tumors. Igarashi et al 11 reviewed 333 patients with 1997 T1N0M0 RCC. They proposed a cutoff size of 4.0 cm for dividing T1 tumors into T1a and T1b subclasses because this cutoff maximized the difference in disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…Existe uma nova corrente propondo ponto de corte em 4 cm e a modificação do atual estádio T1 (TNM 97) para T1a e T1b [7][8][9] , que seria melhor para predizer sobrevida câncer específica e livre de doença otimizando o prognóstico 9 . Nós aderimos a este grupo, pois pacientes com tumores inferiores a 4 cm poderiam prescindir do seguimento pós-operatório, se confirmados critérios de bom prognóstico, como já foi proposto anteriormente 21 .…”
Section: Discussionunclassified
“…Nós aderimos a este grupo, pois pacientes com tumores inferiores a 4 cm poderiam prescindir do seguimento pós-operatório, se confirmados critérios de bom prognóstico, como já foi proposto anteriormente 21 . Como os tumores menores de 4 cm raramente apresentam características de mau prognóstico e o estudo do grau nuclear e invasão microvascular exigem análise multivariada, ao passo que o tamanho tumoral já pode ser mensurado antes da cirurgia e tem valor progóstico 9 , o ponto de corte de 4 cm servirá para otimizar as relações entre tamanho tumoral e os outros caracteres de mau prognóstico. A sobrevida em cinco anos para tumores de alto grau é de 46% 26 e gânglios comprometidos equivalente a 33% 2 , já a presença de invasão microvascular intratumoral confere chance de progressão da doença em 39% dos casos 27 e a degeneração sarcomatosa proporciona sobrevida média de 49 meses aos PT1 e 6,8 meses aos demais estádios da doença 26 .…”
Section: Discussionunclassified
See 1 more Smart Citation